A COMPREHENSIVE STUDY ON AUTOMATED TESTING WITH THE SOFTWARE LIFECYCLE - ALI, HUSSEIN MOHAMMED; HAMZA, MAHMOOD YASHAR; RASHID, TARIK AHMED (Journal of Duhok University, 2023)
The software development lifecycle depends heavily on the testing process, which is an essential part of finding issues and reviewing the quality of software. Software testing can be done in two ways: manually and automatically. With an emphasis on its primary function within the software lifecycle, the relevance of testing in general, and the advantages that come with it, this article aims to give a thorough review of automated testing. Finding time- and cost-effective methods for software testing. The research examines how automated testing makes it easier to evaluate software quality, how it saves time as compared to manual testing, and how it differs from each of them in terms of benefits and drawbacks. The process of testing software applications is simplified, customized to certain testing situations, and can be successfully carried out by using automated testing tools.